Value Added Tax (VAT) in the Indonesian Digital Economy : An Appropiate Solution? - Lita Hepika Ginting; Andini Syahputri; Nailla Yuwanadlin; Khairun Niswa; Roma Grecia Simamora; Galih Supraja (International Journal of Economic Research and Financial Accounting, 2025)
The rapid digital transformation has brought significant changes to economic transactions, necessitating adaptive tax policies capable of accommodating cross-border digital business models. This research employs a qualitative approach with descriptive and analytical methods, integrating doctrinal legal analysis, a comparative approach, and policy analysis. Data were gathered through an in-depth review of relevant Indonesian legal instruments, including Law No. 2/2020 and Minister of Finance Regulations No. 48/2020, No. 60/2022, and No. 199/PMK.10/2019. Additionally, the study references international guidelines such as the OECD International VAT/GST Guidelines (2017) and the BEPS 2.0 framework to provide comparative and global perspectives. The findings reveal that Indonesia’s implementation of VAT on digital transactions has seen significant progress, particularly through the vendor collection model for foreign digital service providers. This policy is expected to enhance tax compliance and expand the digital tax base. However, the study also identifies several challenges, including administrative feasibility, complexity in tax reporting by digital businesses, and the need for harmonization with international standards. From a policy perspective, VAT on Indonesia’s digital economy is deemed relevant in ensuring fiscal fairness, increasing state revenue, and fostering healthy business competition. The study’s limitation lies in its reliance on secondary documentary data, which may not fully capture the practical dynamics faced by businesses and consumers on the ground. Therefore, future research is recommended to incorporate empirical data through interviews or surveys with digital business actors, tax practitioners, and policymakers, to obtain a more nuanced and comprehensive understanding. Overall, this research makes a significant contribution to academic discourse and public policy related to digital economy taxation in Indonesia and serves as a reference for future tax policy reforms in the rapidly evolving digital era.